Developing biological standards for vaccine evaluation. (August 2017) - Page, Mark; Wilkinson, Dianna E; Mattiuzzo, Giada; Efstathiou, Stacey; Minor, Philip
This perspective describes the process of producing biological reference standards, explains why they are needed, who should use them and in what situations. The aim of this perpective is to promote their use at an early stage of vaccine development and to make developers aware of the advantages in doing so.